Protest and Apology in the Arctic: Enacting Citizenship in Two Recent Swedish Films - Lydia Kokkola; Annbritt Palo; Lena Manderstedt (Humanities, 2019)
Today, Sweden enjoys a positive international reputation for its commitment to human rights issues, for instance, in relation to the recent migrant crisis. Abuses committed by the Swedish state against certain ethnic groups within the country are less well known, both within and beyond its borders. These included systematic attempts to curtail the use of indigenous and local languages, thereby causing communicative and ideological rifts between children and their parents. These policies were enacted through the school system from the 1920s until the 1970s, and particularly affected people living in the Arctic region where the national borders are disputed. In this article, we examine two twenty-first-century films set during this era, featuring feisty female characters responding to the school policy. Elina: As though I wasn’t there is a children’s film created by people “outside” the cultural group represented; and Sámi Blood features an adolescent protagonist (and her older self), created by “insiders” of the cultural group represented. In both films, the female protagonists’ relative lack of agency within the state school system is contrasted with their powerful connections to the Arctic landscape. We seek to examine how these films contribute to the work of apology, beginning with a public acknowledgement of the wrongs of the past. Whilst one of the films concludes with a celebration of the female protagonists’ agency, the other proffers a more ambiguous portrayal of power in relation to culture, nationality, and identity.